Effects of Strands Pre-treatment and Adhesive Type on the Properties of Oriented Strand Board Made from Gmelina (Gmelina arborea) Wood - Aisyah, Siti; Haryadi, Januar; Maulana, Muhammad Iqbal; Marwanto; Prasetia, Denni; Hidayat, Wahyu; Lubis, Muhammad Adly Rahandi; Kim, Nam Hun; Febrianto, Fauzi (Jurnal Sylva Lestari, 2021)
The objective of this study was to evaluate the effects of steam treatment of strands on the physical and mechanical properties of oriented strand board (OSB) from gmelina wood (Gmelina arborea) bonded with two types of adhesive. Strands of gmelina wood were steamed at 126°C and pressure of 0.14 MPa for 1 h. OSBs were prepared with a 0.6 g/cm3 target density using two types of adhesives, namely methylene diphenyl diisocyanate (MDI) and phenol-formaldehyde (PF) resins. The resin content used was 5% for MDI and 10% for PF. The physical and mechanical properties of the OSB were evaluated referring to the JIS A 5908-2003 standard, and the values were compared with CSA 0437.0 (Grade O-1) standard. The results showed that the steam treatment improved the dimensional stability of OSB, as shown from the decrease of water absorption and thickness swelling. Steam treatment also increased the mechanical properties of the OSB, such as modulus of elasticity, modulus of rupture, internal bonding strength, and screw holding power. The results revealed that gmelina wood OSB bonded with MDI adhesives produced better OSB than bonded with PF resin. Keywords: gmelina, methylene diphenyl diisocyanate, oriented strand board, phenol-formaldehyde, steam treatment